2011
DOI: 10.1007/s00520-011-1208-7
|View full text |Cite
|
Sign up to set email alerts
|

Awareness of dying: it needs words

Abstract: PurposeThe purpose of this research is to study to what extent dying patients are aware of the imminence of death, whether such awareness is associated with patient characteristics, symptoms and acceptance of dying, and whether medical records and nurses’ and family caregivers’ views on patients’ awareness of dying agree.MethodsNurses and family caregivers of 475 deceased patients from three different care settings in the southwest Netherlands were requested to fill out questionnaires. The two groups were aske… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
32
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(35 citation statements)
references
References 30 publications
2
32
1
Order By: Relevance
“…The frequency of death rattle in our study (66%) is consistent with others [14,[30][31][32]. Consequently, their absence cannot rule out imminent death, but their presence can be highly informative.The positive LRs for pulselessness of radial artery, decreased urine output, Cheyne-Stokes breathing, respiration with mandibular movement, and death rattle were particularly high.…”
Section: Discussionsupporting
confidence: 80%
“…The frequency of death rattle in our study (66%) is consistent with others [14,[30][31][32]. Consequently, their absence cannot rule out imminent death, but their presence can be highly informative.The positive LRs for pulselessness of radial artery, decreased urine output, Cheyne-Stokes breathing, respiration with mandibular movement, and death rattle were particularly high.…”
Section: Discussionsupporting
confidence: 80%
“…Patient awareness of and being at peace with approaching death were correlated with higher QOD scores, which also has been found elsewhere. 46 In 77% of all studied cases, patients died in the presence of family, which was more than that reported in studies in hospitals in New Zealand and France, where 60% and 34% of deceased patients, respectively, died with family present. 3,9 Presence at the moment of death was not strongly related to QOD; relatives gave more weight to saying good-bye.…”
Section: Main Findings and Comparison With Other Studiescontrasting
confidence: 50%
“…45 The difference between physician's awareness and relative's and patient's awareness might be correlated with problematic communication but also to variation in the interpretation of what ''imminent death'' entails. 46,47 Whether and how physicians actually informed relatives about the patient's imminent death was not assessed and might differ from relatives' reports. 48 It has previously been shown that communication between physicians and patients or relatives about a poor prognosis and imminent death is often problematic.…”
Section: Main Findings and Comparison With Other Studiesmentioning
confidence: 99%
“…Shortcomings and barriers have been reported in communication at the end of life between patients and healthcare professionals, and among the staff [40,[41][42][43]. Nurses consider communication at the end of life, although difficult, to be part of their responsibility; education has been found to contribute to increased confidence in interdisciplinary communication and communication with dying patients [29][30][31]37,41,[44][45][46].…”
Section: Discussionmentioning
confidence: 99%